2021
DOI: 10.1038/s41420-021-00760-1
|View full text |Cite
|
Sign up to set email alerts
|

Retinal ganglion cell loss in an ex vivo mouse model of optic nerve cut is prevented by curcumin treatment

Abstract: Retinal ganglion cell (RGC) loss is a pathologic feature common to several retinopathies associated to optic nerve damage, leading to visual loss and blindness. Although several scientific efforts have been spent to understand the molecular and cellular changes occurring in retinal degeneration, an effective therapy to counteract the retinal damage is still not available. Here we show that eyeballs, enucleated with the concomitant optic nerve cut (ONC), when kept in PBS for 24 h showed retinal and optic nerve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 64 publications
2
16
0
Order By: Relevance
“…The total number of animals used in this study was 60. Animals were sacrificed, and their eyes were harvested according to our ex vivo model of retinal degeneration induction [ 15 ]. The enucleated eyeballs were used freshly (WT) or injected with different treatments: Ctr: dimethyl sulfoxide (DMSO, 0.05%), or Curcuma extracts: Cur 5 or 10 μ M (Linnea, cat# CUM 1259), or memantine: Mem 10 μ M (ChemCruz, cat# SC-203628), or citicoline: Cit 100 μ M (Santa Cruz, cat# SC-300380), or ginkgolic acid: GA 20 μ M (Calbiochem, cat# 345887).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The total number of animals used in this study was 60. Animals were sacrificed, and their eyes were harvested according to our ex vivo model of retinal degeneration induction [ 15 ]. The enucleated eyeballs were used freshly (WT) or injected with different treatments: Ctr: dimethyl sulfoxide (DMSO, 0.05%), or Curcuma extracts: Cur 5 or 10 μ M (Linnea, cat# CUM 1259), or memantine: Mem 10 μ M (ChemCruz, cat# SC-203628), or citicoline: Cit 100 μ M (Santa Cruz, cat# SC-300380), or ginkgolic acid: GA 20 μ M (Calbiochem, cat# 345887).…”
Section: Methodsmentioning
confidence: 99%
“…Different methods are mimicking retina degeneration and RGC death. Recently, in our lab, we optimized an ex vivo model of retinal degeneration by cutting the optic nerve (ONC) that could replicate the retinal degeneration and represents a valuable model for primary screening of different compounds against retinal degeneration and RGC death [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same study, it was also observed that curcumin inhibited pro-apoptotic factors, such as caspase-3 and Bax, and upregulated the anti-apoptotic factor Bcl-2 [169]. In an ex vivo optic nerve injury model, thinning of retinal layers, especially the GCL, and strong RGC apoptosis were observed after 24 h post-injury, which correlated with a time-dependent increase in caspase-3 and -9 and pro-apoptotic marker levels, and a powerful activation of the JNK, c-Jun and ERK signaling (MAPK) pathways [170]. Curcumin prevented alterations in the apoptotic cascade and MAPK pathways, preserving RGC survival and retinal thickness [170].…”
Section: Crocus Sativus L-crocetin and Crocinmentioning
confidence: 99%
“…In an ex vivo optic nerve injury model, thinning of retinal layers, especially the GCL, and strong RGC apoptosis were observed after 24 h post-injury, which correlated with a time-dependent increase in caspase-3 and -9 and pro-apoptotic marker levels, and a powerful activation of the JNK, c-Jun and ERK signaling (MAPK) pathways [170]. Curcumin prevented alterations in the apoptotic cascade and MAPK pathways, preserving RGC survival and retinal thickness [170]. In another experimental study in a rat retinal I/R injury model, curcumin supplementation in the diet for 2 days before I/R was able to protect the retina from ischemic injury [171].…”
Section: Crocus Sativus L-crocetin and Crocinmentioning
confidence: 99%